A Conjecture on Pindar, Pythian 2. 81–82 - Lane, Nicholas (Hyperboreus, 2023)
Heyne’s conjecture at Pythian 2. 82 has become the modern vulgate. This note argues that there are reasons why editors should resist it and instead proposes a new solution to the crux.